FACTORS OF INSPIRATION IN ČENČU JEZUPS’ NOVEL “PĪTERS VYLĀNS” - Purinaša, Ligija (Via Latgalica, 2017)
Čenču Jezups or Dzērkste (real name Jezups Kindzuļs, 1888–1941?) was a Latgalian public figure, agronomist, publicist and writer. Date of his death is unknown – he was arrested in February 1941 by NKVD (People's Commissariat for Internal Affairs), but after that there is no information about his further life. He participated in the Latgalian Awakening movement at the beginning of 20th century. Later J. Kindzuļs was one of the organizers of the Latgalian congress (1917) in Rēzekne and a member of Constitutional Assembly of Latvia (1920–1922). He was an editor of such periodicals as “Latgalīts” (1921), “Latgolas Zemkūpis” (1924–1935), “Latgolas lauksaimnīks” (calendar, 1924–1935). He wrote his novel “Pīters Vylāns” between 1935 and 1941. It was first published in Daugavpils in 1943 by writer and publisher Vladislavs Luocis. Later it was published again in Germany in 1967.Čenču Jezups’ novel “Pīters Vylāns” was analysed by Miķelis Bukšs, Ilona Salceviča, Oskars Seiksts. The mentioned papers reveal the meaning of Latgalian self-confidence, which is disclosed in “Pīters Vylāns”, but unfortunately the author of this novel seems to be forgotten. Therefore the aim of this research is to “decode” factors of inspiration in Čenču Jezups’ novel “Pīters Vylāns” to gain more information about author’s life and his value system.Inspiration is always connected with writer’s life experience. Furthermore, the writer creates his own world. Vladislavs Luocis wrote that J. Kindzuļs planned to write a trilogy (Lōcis 1965: 26), but because of Latvia’s occupation by the Soviet Union this intention was not fulfilled. Factors of inspiration are divided into two groups: literary and non-literary (Lukaševičs 2007: 5). Non-literary factors of inspiration are those connected with J. Kindzuļs’ life (social and political events, education and public activities, private life). Literary and cultural factors of inspiration refer to his interests and Latgalian self-identification.Novel “Pīters Vylāns” was written during the authoritarian regime of Kārlis Ulmanis (1934–1940) and deals with peasants’ life during the Russian Revolution of 1905 (1905–1907) in Latgale. The problems of Latgalian identity (to be russified or polonized, quest for identity as a possibility) are dealt with by means of such characters as Vera Semjonova, Stefa, Meikuls Stumbris and Buks. It may be that the characters Pīters Vylāns and Ontons Sleižs are the two sides of J. Kindzuļs’ alter ego. His life experience until World War I is revealed in Pīters Vylāns, but after 1920 – in Ontons Sleižs. J. Kindzuļs may have studied either agronomy or law in Petersburg (after 1907). He took part in Latgalian Musical society and later he worked in the editorial office of newspaper “Drywa” (1908–1912). J. Kindzuļs was involved in the First World War and after that he worked in Rēzekne Commerce School (1919). After 1922 he started farming in his household “Pelēķi” in Laucesa rural municipality and was busy with issues of agronomy in Latgale.J. Kindzuļs’ private life is revealed in two women characters: Elvira and Stefa. Kindzuļs himself had three wives: unknown (married before 1919), Hortenzija Kindzule (Dardedze, married about 1921), Jadviga Kindzule (Kondrāte, married before 1933). J. Kindzuļs became a widower twice. He had two sons: Česlavs (from his first marriage) and Andrivs Jēkabs (from the second marriage). The third child was a daughter, but he and his wife Jadviga lost her because she died of an illness when she was 3.Because of lack of information about J. Kindzuļs, there is no possibility to find out his interests. The only way to get more information about J. Kindzuļs is to research his novel “Pīters Vylāns”. From the novel we know that for J. Kindzuļs there are three groups of literary and cultural factors of inspiration. Firstly, it is Latgalian self-confidence, which appears in the use of Roman Catholic elements such as rites, prayers and honour songs for God. Secondly, it is syncretism of Christian faith and paganism, which is presented as rewriting of folksongs by hand and “vakariešona” or evening gathering. Thirdly, it is European culture, because it is clear that J. Kindzuļs knew, for example, such writers as Goethe, Dostoevsky, Tolstoy, classical music (F. F. Chopin) and architecture. The amount of information about J. Kindzuļs must be enriched and research must be continued. Novel “Pīters Vylāns” was written after 1935 and it is autobiographical. Such characters as Pīters Vylāns and Ontons Sleižs reflect the personality of J. Kindzuļs, but Elvira and Stefa reveal some traits of his wives Hortenzija and Jadviga. J. Kindzuļs glorifies values which became significant after 1934: land and farming, peasants and unity. He describes the Latvians of Latgale during the Russian Revolution of 1905 (1905–1907), but at the same time he criticizes the tendency to be latvianized. The same attitude he has to russification. He accepts the ideological course of Kārlis Ulmanis policy and this ideological position of J. Kindzuļs is manifested as a form of rebellion.